Dexamethasone induces rapid serine-phosphorylation and membrane translocation of annexin 1 in a human folliculostellate cell line via a novel nongenomic mechanism involving the glucocorticoid receptor, protein kinase C, phosphatidylinositol 3-kinase, and mitogen-activated protein kinase. - Solito, E; Mulla, A; Morris, J; Christian, H; Flower, R; Buckingham, J (2003)
Our recent studies on rat pituitary tissue suggest that the annexin 1 (ANXA1)-dependent inhibitory actions of glucocorticoids on ACTH secretion are effected via a paracrine mechanism that involves protein kinase C (PKC)-dependent translocation of a serine-phosphorylated species of ANXA1 (Ser-P-ANXA1) to the plasma membrane of the nonsecretory folliculostellate cells. In the present study, we have used a human folliculostellate cell line (PDFS) to explore the signaling mechanisms that cause the translocation of Ser-P-ANXA1 to the membrane together with Western blot analysis and flow cytometry to detect the phosphorylated protein. Exposure of PDFS cells to dexamethasone caused time-dependent increases in the expression of ANXA1 mRNA and protein, which were first detected within 2 h of steroid contact. This genomic response was preceded by the appearance within 30 min of substantially increased amounts of Ser-P-ANXA1 and by translocation of the phosphorylated protein to the cell surface. The prompt membrane translocation of Ser-P-ANXA1 provoked by dexamethasone was inhibited by the glucocorticoid receptor, antagonist, mifepristone, but not by actinomycin D or cycloheximide, which effectively inhibit mRNA and protein synthesis respectively in our preparation. It was also inhibited by a nonselective PKC inhibitor (PKC(9-31)), by a selective inhibitor of Ca(2+)-dependent PKCs (Go 6976) and by annexin 5 (which sequesters PKC in other systems). In addition, blockade of phosphatidylinositiol 3-kinase (wortmannin) or MAPK pathways with PD 98059 or UO 126 (selective for MAPK kinse 1 and 2) prevented the steroid-induced translocation of Ser-P-ANXA1 to the cell surface. These results suggest that glucocorticoids induce rapid serine phosphorylation and membrane translocation of ANXA1 via a novel nongenomic, glucocorticoid receptor-dependent mechanism that requires MAPK, phosphatidylinositiol 3-kinase, and Ca(2+)-dependent PKC pathways.